Indian adolescents' perceptions of the home food environment - Neha Rathi; Lynn Riddell; Anthony Worsley (BMC, 2018)
Abstract Background The home food environment has the potential to influence the eating behaviour of adolescents. This investigation aimed to understand Indian adolescents' perspectives of their home food environments. Methods Adolescents aged 14-16 years (n = 1026, 65.3% girls) attending private secondary schools in Kolkata completed a paper-based questionnaire during school time which included questions about family food rules, availability and accessibility of foods at home, and domestic cooking responsibility. Boys' and girls' opinions and experiences were compared through cross-tabulation analyses. Results Almost all the adolescents reported that fruits (91.6%) and vegetables (95.7%) were always available in their homes. Approximately two-fifths reported that sugar-sweetened beverages (36.2%) and salty snack foods (38.0%) were readily available. In 56.1% households, adolescents were expected to follow certain food rules during mealtimes (e.g. not talking with my mouth full). The majority of the respondents (80.4%) identified mothers as the primary meal providers, only a minority reported that fathers (5.1%) were responsible for preparation of family meals. Conclusion This understanding of the family-environmental determinants of adolescent dietary habits provides useful directions for nutrition promotion interventions. Health and educational professionals associated with adolescents could communicate about the development of healthy home food environments to provide positive health benefits for adolescents and their families.